1982
DOI: 10.1128/jvi.43.2.456-464.1982
|View full text |Cite
|
Sign up to set email alerts
|

Charge microheterogeneity of the major capsid protein of polyoma virus

Abstract: The behavior in isoelectric focusing of the major capsid polypeptide VP1 of several strains of polyoma virus was studied. Two previously recognized phenomena were reexamined, namely, (i) the separation of the VP1 polypeptide into multiple subspecies differing only slightly from each other in apparent isoelectric point and (ii) strain differences in the overall apparent net charge of the family of VP1 subspecies. It was found that the pattern of subspecies was reproducible when focusing was initiated from eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It may result from additional, as yet uncharacterized, posttranslational modifications such as acetylation, carboxylation or decarboxylation, sulfation, methylation, etc. Alternatively, it has been suggested that some of the heterogeneity may result fom conformational differences, protein-protein interactions, or ampholyte binding (20). We are continuing to investigate this important question.…”
Section: Discussionmentioning
confidence: 98%
“…It may result from additional, as yet uncharacterized, posttranslational modifications such as acetylation, carboxylation or decarboxylation, sulfation, methylation, etc. Alternatively, it has been suggested that some of the heterogeneity may result fom conformational differences, protein-protein interactions, or ampholyte binding (20). We are continuing to investigate this important question.…”
Section: Discussionmentioning
confidence: 98%
“…Isoelectric focusing of disrupted polyomavirus virions resolves at least six isospecies, which have been designated A through F (3,19,20). Earlier work performed in our laboratory suggested that the phosphorylated species D, E, and F, which together comprise only about 12 to 15% of the total VP1 present in polyomavirus virions, perform the functions of viral hemagglutinin and receptor (3).…”
mentioning
confidence: 98%